Assessment of Breast Specimens With or Without Calcifications in Diagnosing Malignant and Atypia for Mammographic Breast Microcalcifications Without Mass: A STARD-Compliant Diagnostic Accuracy Article. Issue 42 (October 2015) - Cheung, Yun-Chung; Juan, Yu-Hsiang; Ueng, Shir-Hwa; Lo, Yung-Feng; Huang, Pei-Chin; Lin, Yu-Ching; Chen, Shin-Cheh
Abstract : Abstract: Presence of microcalcifications within the specimens frequently signifies a successful attempt of stereotactic vacuum-assisted breast biopsy (VABB) in obtaining a pathologic diagnosis of the breast microcalcifications. In this study, the authors aimed to assess and compare the accuracy and consistency of calcified or noncalcified specimens obtained from same sites of sampling on isolated microcalcifications without mass in diagnosing high-risk and malignant lesions. To the best of our knowledge, an individual case-based prospective comparison has not been reported. With the approval from institutional review board of our hospital (Chang Gung Memorial Hospital), the authors retrospectively reviewed all clinical cases of stereotactic VABBs on isolated breast microcalcifications without mass from our database. The authors included those having either surgery performed or had clinical follow-up of at least 3 years for analysis. All the obtained specimens with or without calcification were identified using specimen radiographs and separately submitted for pathologic evaluation. The concordance of diagnosis was assessed for both atypia and malignant lesions. A total of 390 stereotactic VABB procedures (1206 calcified and 1456 noncalcified specimens) were collected and reviewed. The consistent rates between calcified and noncalcified specimens were low for atypia and malignant microcalcifications (44.44% in flat epithelial atypia, 46.51% in atypical ductal hyperplasia, 55.73% in ductal carcinoma in situ, and 71.42% in invasive ductal carcinoma). The discordance in VABB diagnoses indicated that 41.33% of malignant lesions would be misdiagnosed by noncalcified specimens. Furthermore, calcified specimens showed higher diagnostic accuracy of breast cancer as compared with the noncalcified specimens (91.54 % versus 69.49%, respectively). The evaluation of both noncalcified specimens and calcified specimens did not show improvement of diagnostic accuracy as compared with evaluating calcified specimens alone (91.54% versus 91.54%, respectively). The high prevalence of diagnostic discordance between the calcified and noncalcified specimens indicated the higher value of calcified specimens in diagnosing atypia and malignant microcalcifications. Noncalcified specimens did not provide additional diagnostic benefit from this study. The separation of calcified and noncalcified specimens may facilitate more focused interpretation from pathologists among the large number of specimens.